Preheating System of Auxiliary Converter for Plateau Type HXD1C Locomotive - WU Jianxiong; CHEN Xiang; QIAN Yongliang (Kongzhi Yu Xinxi Jishu)
It illustrated the preheating system of auxiliary converter for plateau type HXD1C locomotive and its logic control process. It analyzed the methods of selecting preheating resistance, designing air-channels and installing sensors, which provided important reference for ensuring that the auxiliary converter could run normally and steadily under the extreme cold condition.